Bazedoxifene, a new orphan drug for the treatment of bleeding in hereditary haemorrhagic telangiectasia - Zarrabeitia, Roberto; Ojeda-Fernandez, Luisa; Recio, Lucia; Bernabéu, Carmelo; Parra, José A.; Albiñana, Virginia; Botella, Luisa M. (Thrombosis and Haemostasis, 2016)
Hereditary haemorrhagic telangiectasia (HHT), or Rendu-Osler-Weber syndrome, is a dominant genetic vascular disorder. In HHT, blood vessels are weak and prone to bleeding, leading to epistaxis and anaemia, severely affecting patients’ quality of life. Development of vascular malformations in HHT patients is originated mainly by mutations in ACVRL1/ALK1 (activin receptor-like kinase type I) or Endoglin (ENG) genes. These genes encode proteins of the TGF-β signalling pathway in endothelial cells, controlling angiogenesis. Haploinsufficiency of these proteins is the basis of HHT pathogenicity. It was our objective to study the efficiency of Bazedoxifene, a selective estrogen receptor modulator (SERM) in HHT, looking for a decrease in epistaxis, and understanding the underlying molecular mechanism. Plasma samples of five HHT patients were collected before, and after 1 and 3 months of Bazedoxifene treatment. ENG and ALK1 expression in activated mononuclear cells derived from blood, as well as VEGF plasma levels, were measured. Quantification of Endoglin and ALK1 mRNA was done in endothelial cells derived from HHT and healthy donors, after in vitro treatment with Bazedoxifene. Angiogenesis was also measured by tubulogenesis and wound healing assays. Upon Bazedoxifene treatment, haemoglobin levels of HHT patients increased and the quantity and frequency of epistaxis decreased. Bazedoxifene increased Endoglin and ALK1 mRNA levels, in cells derived from blood samples and in cultured endothelial cells, promoting tube formation. In conclusion, Bazedoxifene seems to decrease bleeding in HHT by partial compensation of haploinsufficiency. The results shown here are the basis of a new orphan drug designation for HHT by the European Medicine Agency (EMA).
Keywords: Bazedoxifene; selective estrogen receptor modulator; ENG protein; ALK1 protein; hereditary haemorrhagic telangiectasia